Efektivitas kebijakan pemerintah daerah dalam pengembangan kelembagaan agribisnis lokal domba di Kabupaten Sukabumi, Jawa Barat: The effectiveness of local government policies in developing local sheep agribusiness institutions in Sukabumi Regency, West Java - Rusdiana, Supardi; Ramdani, Diky; Yunasaf, Unang; Talib, Chalid; Adawiyah, Cut Rabiatul; Amam (Analisis Kebijakan Pertanian, 2025)
Sheep farming is an agribusiness that can contribute to the provision of animal protein and rural economic development. This study aims to analyze local government policies to develop a sheep farming agribusiness institution to improve business performance and competitiveness. The study was conducted in Sukabumi Regency, West Java, and data were collected using mixed-methods approaches, including quantitative surveys, in-depth interviews, and focus group discussions. Data were analyzed quantitatively and qualitatively to measure productivity, cost efficiency, market access, and farmer income. The results show that good local agribusiness institutional performance and the high effectiveness of local government policy implementation significantly influence the economic competitiveness of sheep farming. Technical efficiency increased after a synergy between institutional actors developed, as indicated by a 50% increase in daily weight gain of sheep, a 17% decrease in feed conversion ratio, and a 17% decrease in feed costs. From a market perspective, access to formal marketing channels increased from 20% to 65%, accompanied by diversification of distribution channels and an increase in the volume of processed products. Socio-economic impacts include a more than doubling of net income, a 30-point increase in women’s participation, and an 88% business sustainability rate. This research confirms that local agribusiness institutions play a strategic role in strengthening the business performance and economic competitiveness of sheep farmers. The results recommend that, to support the sustainability of sheep farming, the local government needs to implement institutional capacity-building, the digitalization of agribusiness services, and improvements in infrastructure and connectivity between villages.